Engineering applications : analytical and numerical calculation with MATLAB - Dupac, Mihai; Marghitu, Dan B. (John Wiley & Sons, Inc., 2021)
"Engineering mechanics involves the development of mathematical models of the physical world. MATLAB is a computational tool that has transformed mathematical and physical calculation methods. This is because MATLAB not only provides numerical calculations but also facilitates real-time analytical calculations. MATLAB is therefore very useful in the process of deriving solutions for any problem in machine design. MATLAB is also more generally useful because using computational simulations allows readers to visualize processes through symbolic and numerical computation"--